2014, No. 15, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Financial accounting challengesMarta Lapková, Jana Stašová, Recognition of comprehensive income in Slovak companies, 8Inga Bumane, Accounting policy in Latvia – existing main rules and current trends, 15Neringa Stončiuvienė, Danutė Zinkevičienė, Comparative analysis of company performance result financial statements, 30Birutė Gudonytė, Kristina Rudžionienė, The relationship between the financial crisis and the measurement of fair value in financial statements, 43Ieva Vaičiulytė, Kristina Rudžionienė, Peculiarities of enterprise equity and equity accounting, 52Corporate social responsibility and information disclosureRamunė Budrionytė, The disclosure of information about organization social responsibility in financial statements: benefits and opportunities, 63Inga Karlonaitė, Kristina Rudžionienė, Quality assessment model of environmental information disclosure, 76Vytautė Petraškaitė, Kristina Rudžionienė, The disclosure of corporate social responsibility which is presented in the financial information on the internet, 88Tomas Baležentis, Romualdas Valkauskas, The use of the farm accountancy data network for estimation of the optimal family farm size according to the microeconomic theory, 101Tendencies of management accountingMarija Kučinskienė, Regina Jakiūnienė, The system of integrated activities evaluation – possibility for successful business processes management, 113Daiva Tamulevičienė, Responsibility centres in the system of controlling, 126Vilius Savickas, Julija Šarupičiūtė, Factors influencing the target costing process, 141
Keywords: none